Base Excision Repair of N(6)-Deoxyadenosine Adducts of 1,3-Butadiene - Wickramaratne, Susith (Biochemistry, 2016)
The important industrial and environmental carcinogen, 1,3-butadiene (BD), forms a range of adenine adducts in DNA, including N(6)-(2-hydroxy-3-buten-1-yl)-2′-deoxyadenosine (N(6)-HB-dA), 1,N(6)-(2-hydroxy-3-hydroxymethylpropan-1,3-diyl)-2′-deoxyadenosine (1,N(6)-HMHP-dA), and N(6),N(6)-(2,3-dihydroxybutan-1,4-diyl)-2′-deoxyadenosine (N(6),N(6)-DHB-dA). If not removed prior to DNA replication, these lesions can contribute to A → T and A → G mutations commonly observed following exposure to BD and its metabolites. In the present study, base excision repair of BD-induced 2′-deoxyadenosine (BD-dA) lesions was investigated. Synthetic DNA duplexes containing site- and stereospecific S-N(6)-HB-dA, R,S-1,N(6)-HMHP-dA, and R,R-N(6),N(6)-DHB-dA adducts were prepared by a post-oligomerization strategy. Incision assays with nuclear extracts from human fibrosarcoma (HT1080) cells have revealed that BD-dA adducts were recognized and cleaved by a BER mechanism, with relative excision efficiency in the order: S-N(6)-HB-dA > R,R-N(6),N(6)-DHB-dA > R,S-1,N(6)-HMHP-dA. Strand cleavage at the adduct site was decreased in the presence of BER inhibitor methoxyamine and by competitor duplexes containing known BER substrates. Similar strand cleavage assays conducted using several eukaryotic DNA glycosylases/lyases [AAG, Mutyh, hNEIL1, and hOGG1] have failed to observe correct incision products at the BD-dA lesion sites, suggesting that a different BER enzyme may be involved in the removal of BD-dA adducts in human cells.